2017
DOI: 10.1186/s12879-016-2136-4
|View full text |Cite
|
Sign up to set email alerts
|

HPV Genotypes distribution in Indian women with and without cervical carcinoma: Implication for HPV vaccination program in Odisha, Eastern India

Abstract: BackgroundConsidering the limited cross protection offered by the current HPV vaccines, understanding the HPV genotype distribution among the different population is essential in predicting the efficacy of current vaccine and devising new vaccine strategy. The present work aimed at investigating the HPV genotypes distribution among women with and without cervical carcinoma in Odisha, Eastern India.MethodsA total of 607 participants have been enrolled between January 2014 and June 2016. L1-PCR, sequencing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 39 publications
2
49
2
Order By: Relevance
“…We found HPV-16 and 18 to be associated with 87% of the total CC tissue samples in our study, consistent with a previous study of 54 Nepalese cases detecting HPV-16/18 in 90% of samples [ 20 ] . Our study detected HPV-16/18 at a moderately higher rate than previously reported for Southern Asia (80%) [ 21 ], and the Asian region (71%) in a worldwide study [ 12 ] , but a little smaller than those rates from Eastern India that exceeds 100%, considering multiple infections (HPV-16: 83.78%; HPV-18, 21.08%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 56%
“…We found HPV-16 and 18 to be associated with 87% of the total CC tissue samples in our study, consistent with a previous study of 54 Nepalese cases detecting HPV-16/18 in 90% of samples [ 20 ] . Our study detected HPV-16/18 at a moderately higher rate than previously reported for Southern Asia (80%) [ 21 ], and the Asian region (71%) in a worldwide study [ 12 ] , but a little smaller than those rates from Eastern India that exceeds 100%, considering multiple infections (HPV-16: 83.78%; HPV-18, 21.08%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 56%
“…It is important to determine the epidemiology of mono- and coinfections of HPV in order to establish appropriate prevention strategies for the design of novel vaccines based on each population. Determining the epidemiology of mono- and coinfections of HPV has been instrumental in establishing appropriate prevention strategies for the design of new vaccines tailored to each population [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…30,31 The interesting lack of HPV in this ethnic group lends some support to a true low prevalence of HPV in ESCC in Malaysians. When taken in the face that studies from India have generally reported the substantial prevalence of HPV in their patients with esophageal cancer, 6,32,33 while the rates of HPV infection in cervical cancers in Malaysia and India [34][35][36][37] are similar, our observation may again argue for a true low predilection of HPV for ESCC in Malaysians. Certainly, the possibility that the higher prevalence observed in some studies and the low prevalence in our case may be a result of variable methodology stringencies 8,10 cannot be completely excluded.…”
Section: Discussionmentioning
confidence: 52%